1984
DOI: 10.1016/0304-3959(84)90112-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal sensibility changes during ischemie nerve block

Abstract: Changes in perception of pure thermal stimuli delivered to the hand at threshold intensity were observed during ischemic nerve block in 27 healthy subjects in order to study the significance of unmyelinated cutaneous cold receptors for thermal sensibility. Paresthesias and an increasing feeling of numbness were followed by a sudden change in cold sensation which developed a clearly dysesthetic quality. When complete motor block was reached and no myelinated axon functions were left, cold stimuli were still cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 14 publications
3
69
1
1
Order By: Relevance
“…Convincing evidence that stimulation from cold fibers inhibits cold-induced nociceptive stimulation comes from the aforementioned studies of ischemic or pressure block of A-δ cold fibers, which causes innocuous cooling to be felt as stinging, burning or hot (Fruhstorfer 1984;Kojo and Pertovaara 1986;Wahren et al 1989;Yarnitsky and Ochoa 1990). Evidence that nociceptive stimulation might also be inhibited by stimulation of warm fibers (Kanui 1987) comes from the present finding that 33% of all spots within heat-sensitive thermal sites were nociceptive spots (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…Convincing evidence that stimulation from cold fibers inhibits cold-induced nociceptive stimulation comes from the aforementioned studies of ischemic or pressure block of A-δ cold fibers, which causes innocuous cooling to be felt as stinging, burning or hot (Fruhstorfer 1984;Kojo and Pertovaara 1986;Wahren et al 1989;Yarnitsky and Ochoa 1990). Evidence that nociceptive stimulation might also be inhibited by stimulation of warm fibers (Kanui 1987) comes from the present finding that 33% of all spots within heat-sensitive thermal sites were nociceptive spots (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…It has long been known that co-activation of different fiber classes determines the sensory quality. Thus noxious cold stimuli induced more pain and burning sensation when A-fibers were blocked (Fruhstorfer 1984;Yarnitsky and Ochoa 1990). Similarly, the sensations induced by pin pricks during an A-fiber block changed to burning and, sometimes, to pure heat (Koltzenburg et al 1993), suggesting that coactivation of low-threshold mechanoreceptors reduces mechanically induced pain.…”
Section: Co-activation Of Different Fiber Classesmentioning
confidence: 93%
“…From 1975 to 1990, Mackenzie and several other investigators provided a key insight into the neural basis of thermal reception and perception (20)(21)(22)(23). They found that a blockage of myelinated fibers (A-fibers) by ischemia or compression allows cold stimuli to activate non-myelinated C-fibers and to evoke heat or burning sensations.…”
Section: Introductionmentioning
confidence: 99%
“…According to this model, when the skin is stimulated by noxious cold temperatures, both C2 fibers and CMHC fibers will be activated, leading to pain sensation ( Figure 2B). Since cold stimuli evoke a hot or burning pain sensation following a blockage of A-fibers (20)(21)(22)(23), the cold quality of cold pain may be either encoded by an unknown population of myelinated nociceptors that respond to noxious cold or encoded by a transient activation of Aδ-cold fibers ( Figure 2B). Inactivation of Aδ-cold fibers at noxious cold temperatures (18) also removes cold-induced pain inhibition, which in turn allows more C2 fibers to activate the pain pathway.…”
Section: Introductionmentioning
confidence: 99%